Finding Home: A Forensic Perspective on the Global Crisis of Forced Migration - Heristyorini, Ayodya (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2017)
Forced migration is a major social, political, legal, and public health challenge for the world today. Many developed countries are struggling to keep up with the massive influx of refugees streaming in bringing a myriad of issues that need to be addressed. Despite fleeing for their lives when crossing geographical borders, refugees still have the legal burden of validating asylum claims. This paper aims to discuss the different roles that forensic science can partake in managing the global crisis of forced migration. In a legal aspect, the role of forensics is to provide evidence that can aid refugees in their asylum proceedings, such as age estimation for minors, physical and mental health assessments, and investigation of torture allegations. Despite polarising public opinion and many problematic challenges involved in working with refugees, the spirit of forensic science has always been about objectivity without discrimination. It is within the professional duty of forensic experts as members of the global community to contribute what they can in this humanitarian crisis our society is currently facing.